2018
DOI: 10.2174/1871527317666180412153612
|View full text |Cite
|
Sign up to set email alerts
|

N-3 (Omega-3) Fatty Acids: Effects on Brain Dopamine Systems and Potential Role in the Etiology and Treatment of Neuropsychiatric Disorders

Abstract: Clinical studies supporting their role in the etiologies of diseases involving the brain dopamine systems and the potential of n-3 PUFAs in the treatment of these disorders are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 282 publications
1
70
0
3
Order By: Relevance
“…The type of FAs contained in membrane phospholipids may modulate a broad range of biological mechanisms and pathways in the brain, including neurons, glial cells, and endothelial cells integrity and survival, neurotransmission (dopaminergic, serotonergic, glutamatergic, and cholinergic), and neuroinflammation, and [216][217][218]. PUFAs, especially ARA and DHA, are the major constituents of the neuronal membranes.…”
Section: Role Of Unsaturated Fatty Acid Desaturases In Humans and Othmentioning
confidence: 99%
“…The type of FAs contained in membrane phospholipids may modulate a broad range of biological mechanisms and pathways in the brain, including neurons, glial cells, and endothelial cells integrity and survival, neurotransmission (dopaminergic, serotonergic, glutamatergic, and cholinergic), and neuroinflammation, and [216][217][218]. PUFAs, especially ARA and DHA, are the major constituents of the neuronal membranes.…”
Section: Role Of Unsaturated Fatty Acid Desaturases In Humans and Othmentioning
confidence: 99%
“…Omega-3 fatty acids (omega-3 FAs) are polyunsaturated fatty acids, whose primary sources are in oily fish. They are components of neuronal membranes and have a main role in neurotransmission, neuronal development and function [105]. Two of the main omega-3 FAs are docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) and it has been demonstrated that supplementation with omega-3 FAs has beneficial effects in several neurodegenerative and neuropsychiatric disorders such as Parkinson´s and Alzheimer´s diseases, depression, bipolar disorder, anxiety, and schizophrenia [106,107].…”
Section: Omega-3 Fatty Acids Prevent Inflammationmentioning
confidence: 99%
“…Both ω ‐3 LC‐PUFAs and alcohol engage neurotransmitter systems: Deficits in ω ‐3 LC‐PUFAs adversely affect neuroinflammatory mechanisms (Laye et al., ), which in turn impact stress hypothalamic–pituitary–adrenal (HPA) axis sensitivity and other neurotransmitter systems (Levant, ). Effects of ω ‐3 LC‐PUFA deficiencies on dopaminergic neurons can be pronounced, especially in the ventral striatum (Healy‐Stoffel and Levant, ). The dopaminergic system is of central relevance in alcohol responses (Schuckit, ); alcohol also has prominent simultaneous effects on gamma‐aminobutyric acid, glutamate, opioid, serotonin, and acetylcholine systems, and on the HPA axis, each of which could contribute to alcohol sensitivity (Schuckit, ).…”
Section: Discussionmentioning
confidence: 99%